The Conservative Turn in Qur’anic Legal Hermeneutics: Discourse and Authority in Tafsīr Āyāt Al-Aḥkām - Yahya, Ahmad; Zidna Zuhdana Mushthoza (Journal of Ushuluddin and Islamic Thought, 2025)
The article examines Mannā‘ al-Qaṭṭān’s Tafsīr Āyat al-Aḥkām as a central articulation of a conservative turn in Qur’anic legal hermeneutics, formulated to reinforce Islamic orthodoxy amid the growing influence of contextualist approaches in twentieth-century Qur’anic interpretation. Employing Norman Fairclough’s Critical Discourse Analysis framework, this study investigates three levels of discourse practice—text, discourse production, and socio-cultural context—to demonstrate how al-Qaṭṭān’s interpretive strategies construct, sustain, and reproduce religious authority. The textual analysis reveals that al-Qaṭṭān articulates his legal hermeneutics through tarbawī (pedagogical) and taysīrī (facilitative or ease-oriented) orientations, supported by argumentative patterns that reaffirm the boundaries of Islamic orthodoxy. The analysis of discourse production reveals that his critiques of theological groups—such as the Mu‘tazilah, Qadariyyah, Mujassimah-Mushabbihah, and Mu‘aṭṭilah—as well as his positions on contemporary issues, including dhikr jahrī (audible remembrance), population control, and liberal thought, function as mechanisms for delegitimizing alternative interpretive discourses. At the socio-cultural level, the study demonstrates that al-Qaṭṭān’s legal interpretive construction is inseparable from Saudi Arabia’s ideological configuration and the institutional role of the Islamic University of Imam Muḥammad ibn Sa‘ūd in shaping the kingdom’s global da‘wah agenda since the 1960s. The study concludes that his tafsīr serves as a crucial locus for reinforcing orthodoxy and sustaining the authority of conservative discourse in contemporary Islamic legal thought.